2010
DOI: 10.3109/00016481003621546
|View full text |Cite
|
Sign up to set email alerts
|

Does reflux have an effect on nasal mucociliary transport?

Abstract: No statistical difference was found between the saccharine test results of the study group and control group before treatment. The differences between the pretreatment and post-treatment reflux symptom index and reflux finding scores were statistically significant. The difference between the post-treatment saccharine test results of the patients in whom reflux scores returned to normal and those with remaining high scores was not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…The mechanism for this is believed to be due to direct effects of refluxate on nasal/sinus mucosa, although no consistent effect of LPR on nasal mucociliary clearance has been demonstrated. 47 One study found that patients with LPR had higher scores on the Sinonasal Outcome Test (SNOT-20), even in the absence of a diagnosis of CRS, 48 and another study showed that patients with LPR had higher scores for postnasal drainage. 49 Some of this association could be due to overlapping symptoms between LPR and CRS.…”
Section: Humoral or Innate Immune Deficiencymentioning
confidence: 98%
“…The mechanism for this is believed to be due to direct effects of refluxate on nasal/sinus mucosa, although no consistent effect of LPR on nasal mucociliary clearance has been demonstrated. 47 One study found that patients with LPR had higher scores on the Sinonasal Outcome Test (SNOT-20), even in the absence of a diagnosis of CRS, 48 and another study showed that patients with LPR had higher scores for postnasal drainage. 49 Some of this association could be due to overlapping symptoms between LPR and CRS.…”
Section: Humoral or Innate Immune Deficiencymentioning
confidence: 98%
“…25 Durmus et al, measured MCT using saccharin test in 50 cases diagnosed with GERD and LPRD and 30 healthy controls. 26 There was no statistically significant difference between the saccharin transit test results of the study and control group. Wong et al reported that only 0.2% of 809 reflux episodes had reached the nasopharynx using 24h ambulatory pH monitoring in 40 CRS subjects.…”
Section: Discussionmentioning
confidence: 65%
“…However, a study by Durmus et al showed no improvement in symptoms of refractory CRS in patients with PPI. [21] Studies have shown that reflux leads to poor post FESS symptomatic outcomes. [6] In our study also we found that in patients of control group where PPI were not added to treatment, patients had much lesser improvement with FESS alone as treatment as compared to study group.…”
Section: Discussionmentioning
confidence: 99%